Pengaruh Persepsi Manfaat dan Persepsi Kemudahan Penggunaan terhadap Minat Menggunakan Dompet Digital DANA: - Rahmawati, Meliza; Rosa, Aslamia (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This Research aims to analyze the effect of perceived usefulness and perceived ease of use toward intention to use on e-wallet DANA in Generation Z of Palembang City. The sampling technique that used in this research is non-probability sampling with a purposive sampling method. Type of this research is descriptive quantitative. The Population of this research is E-wallet DANA users which belong to Generation Z category. The data was collected through questionnaire which validity and reliability were already verified and distributed to 100 respondents. The analysis tools in this research are simultaneous test (F test), Partial test (t test) and multiple linear regression analysis. The result of F test shows that the TAM’s variables simultaneously affect the Intention to use on user. Keywords: Perceived Usefulness, Perceived Ease of Use, Intention to Use